Complement factor C5a induces atherosclerotic plaque disruptions - Wezel, Anouk (J Cell Mol Med, 2014)
Complement factor C5a and its receptor C5aR are expressed in vulnerable atherosclerotic plaques; however, a causal relation between C5a and plaque rupture has not been established yet. Accelerated atherosclerosis was induced by placing vein grafts in male apoE(−/−) mice. After 24 days, when advanced plaques had developed, C5a or PBS was applied locally at the lesion site in a pluronic gel. Three days later mice were killed to examine the acute effect of C5a on late stage atherosclerosis. A significant increase in C5aR in the plaque was detectable in mice treated with C5a. Lesion size and plaque morphology did not differ between treatment groups, but interestingly, local treatment with C5a resulted in a striking increase in the amount of plaque disruptions with concomitant intraplaque haemorrhage. To identify the potential underlying mechanisms, smooth muscle cells and endothelial cells were treated in vitro with C5a. Both cell types revealed a marked increase in apoptosis after stimulation with C5a, which may contribute to lesion instability in vivo. Indeed, apoptosis within the plaque was seen to be significantly increased after C5a treatment. We here demonstrate a causal role for C5a in atherosclerotic plaque disruptions, probably by inducing apoptosis. Therefore, intervention in complement factor C5a signalling may be a promising target in the prevention of acute atherosclerotic complications.